Polimorfismos genéticos e desempenho físico em jogadores de futebol das categorias de base do São Paulo Futebol Clube - Dionísio, Thiago José (2014)
Literature reports that genetic polymorphisms may determine important modulations on athletes phenotypes, such as height, cardiovascular adaptations, use of energy substrates as well as electrolyte and hormonal balance. It is possible that individuals who express the alpha actinin 3 gene (ACTN3; ancestral homozygous RR or heterozygous RX) may offer advantages in movements that require strength and fast twitch compared with individuals with XX genotype. ACTN3 is a sarcomeric Z line component, which is important for the actin filaments anchorage and myofibrillar arrangement maintenance. Regarding AMP deaminase (AMPD1) polymorphism, it has been reported that athletes with the mutant allele (allele T) may present disadvantages in intense and repetitive physical activities, since the enzyme encoded by this gene is responsible for the ATP resynthesis after intense muscle contractions. Polymorphisms in the angiotensin converting enzyme gene (ACE; deletion allele D) and angiotensinogen (AGT; mutated allele T) may favor athletes in activities requiring strength, due to the fact of higher Angiotensin (Ang) II circulating levels. The present study investigated whether polymorphisms in ACTN3, AMPD1, ACE and AGT genes, alone or in combination, may influence the hemodynamic and cardiac parameters as well as soccer players performance during physical tests such as jump, speed and endurance. Saliva from 220 young professional soccer players (14-20 years) from São Paulo Futebol Clube (Brazil) was collected. Then, total DNA was extracted from saliva and polymerase chain reaction (PCR) was used for genotyping of athletes. To provide more reliability to the study, athletes were also separated according to their age. Before this separation, the athletes with the mutation in the ACTN3 gene jumped lower heights in Squat Jump test (SJ) (RR/RX = 33.64 ± 5.31 vs XX = 30.81 ± 4.51 cm, p = 0.007), as well as in the Under (U)-15 (RR/RX = 34.88 ± 5.39 vs XX = 30.59 ± 4.07 cm, p = 0.04) and U- 17 (RR/RX = 35.82 ± 4.35 vs XX = 30.24 ± 5.16 cm, p = 0.01) categories. In the Counter Movement Jump test (CMJ), RR/RX jumped 37.26 ± 5.72 cm and XX 34.12 ± 4.84 cm (p = 0.005). In the U-17 category, RR/RX jumped 38.56 ± 5.69 cm and XX 32.90 ± 6.06 cm (p = 0.02). In the Counter Movement Jump with arms (CMJb) test, with all athletes, RR/RX jumped 43.85 ± 6.38 cm and XX 40.61 ± 5.06 cm (p = 0.009). The speed test (30 m) showed in the U-17 category that RR/RX were faster than the XX athletes (RR/RX = 4.13 ± 0.13 vs XX = 4.27 ± 0 17 s, p = 0.04). Regarding AMPD1 gene, no significant difference was found in the jumps and endurance tests, but in the speed test (10 m), CC athletes were faster than those with CT/TT genotypes (CC = 1.53 ± 0.19 vs CT/TT = 1.62 ± 0.16 s, p = 0.04). Athletes with DD genotype (ACE) jumped significantly higher in CMJb test compared with ID/II (DD = 44.37 ± 6.22 vs ID/II = 42.35 ± 6.23 cm, p = 0.02). In the U-17 category, DD athletes jumped higher in SJ (DD = 38.04 ± 5.00 vs ID/II = 33.16 ± 4.11 cm, p = 0.01), CMJ (DD = 41.03 ± 5.64 vs ID/II = 35.76 ± 4.26 cm, p = 0.01) and CMJb (DD = 48.62 ± 5.98 vs ID/II = 42.42 ± 4.81 cm, p = 0.007). In the endurance test, athletes from U-16 category with genotypes ID/II, traveled greater distances compared with DD (ID/II = 1.467 ± 63.70 vs DD =1.244 ± 64.25 m, p = 0.04). The DD genotype also favored athletes in speed test (30 m), either for players from U-14 category (DD = 4.29 ± 0.19 vs ID/II = 4.40 ± 0.16 s, p = 0.02) or for the U- 17 category (DD = 4.07 ± 0.15 vs ID/II = 4.20 ± 0.13 s, p = 0.04). AGT gene polymorphism did not influence the performance in the tests, but athletes with the mutant genotype (TT) showed greater left ventricle (LV) hypertrophy (114.6 ± 105.2 g/m2 for TT, 92.16 ± 18.88 g/m2 for MT and 94.78 ± 21.08 g/m2 for MM, p = 0.04) without any change in cardiac and other hemodynamic parameters. Greater LV hypertrophy (DD = 96.95 ± 19.96, ID = 90.14 ± 21.58 and II = 91.67 ± 21.09 g/m2, p = 0.04) and higher ejection fraction (DD = 71.73 ± 7.71, ID = 69.48 ± 6.51 and II = 68.59 ± 5.72 %, p = 0.02) were also found in the athletes with the DD genotype. The analysis of genes combination on athletic performance, when characteristics of strength and muscle fast twitch in the ranking by score were taken into account, showed that athletes with the highest scores (5-8) jumped higher than those with lower scores (1-4) in SJ test (score 5 to 8 = 33.80 ± 5.16 vs score 1 to 4 = 31.60 ± 5.22 cm, p = 0.01) and CMJ test (score 5 to 8 = 43.90 ± 6.85 vs score 1 to 4 = 41.87 ± 5.98 cm, p = 0.04). The present results suggest that RR/RX (ACTN3), DD (ACE) and CC (AMPD1) genotypes may benefit soccer players in activities requiring strength and fast twitch. In addition, ID/II genotypes seem to provide more resistance to athletes in endurance activity. In the future, the organization, standardization and ethical responsibility will be required in the management of these genetic markers for use in athletes training process.